6(2x-3)=24

Simple and best practice solution for 6(2x-3)=24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2x-3)=24 equation:


Simplifying
6(2x + -3) = 24

Reorder the terms:
6(-3 + 2x) = 24
(-3 * 6 + 2x * 6) = 24
(-18 + 12x) = 24

Solving
-18 + 12x = 24

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18' to each side of the equation.
-18 + 18 + 12x = 24 + 18

Combine like terms: -18 + 18 = 0
0 + 12x = 24 + 18
12x = 24 + 18

Combine like terms: 24 + 18 = 42
12x = 42

Divide each side by '12'.
x = 3.5

Simplifying
x = 3.5

See similar equations:

| X+(x-21)=157 | | 2x+12+7x-1=x | | 2(3x+3)=11x+3-5x+3 | | z/(-1)=9 | | -8+x=46 | | X+X-21=157 | | 6.8/(-4)= | | 2x+11x=52+x | | x-(-5)=34 | | 9x+15=5x+1 | | 4*(-4.3)*-2= | | X^2-15x-11000=0 | | 4(x+8)=8x+3-4x+29 | | 4b+3-b=-7+2+b | | 6-3(4x+2)-10x= | | (-X+1)2+(-x-1)2=0 | | k+12/17=2 | | 8x+3=8x+3-4x+29 | | 80x^4-48x^2+4=0 | | 16-2(x-5)= | | -21x+5=-40 | | 11x+13=108 | | half(7x-2)+5=2x+7 | | 3a^2-8a+4=0 | | 3x+8=2x+1 | | 8x-5=8(x+6) | | -7n-3(n+7)=3-6n | | -72-3(n+7)=3-6n | | 7+(-3)v=6+v | | y=hx+f | | 3x^3+14x^2-12x=0 | | 9c+5-6=9 |

Equations solver categories